A Longitudinal Investigation of Inflammatory Markers in Colorectal Cancer Patients Perioperatively Demonstrates Benefit in Serial Remeasurement. Issue 6 (June 2018) - Chan, Joseph C. Y.; Diakos, Connie I.; Chan, David L. H.; Engel, Alexander; Pavlakis, Nick; Gill, Anthony; Clarke, Stephen J.
Abstract : Objective: To characterize the longitudinal course of the systemic inflammatory response (SIR) throughout the perioperative period. To investigate whether postoperative changes in the neutrophil-to-lymphocyte ratio (NLR) or lymphocyte-to-monocyte ratio (LMR) when compared with preoperative levels ('conversion') are associated with survival differences in colorectal cancer patients undergoing resection. Background: Recent evidence suggests that preoperative measurements of markers of the SIR including the NLR and LMR are prognostic. However, a few data exist evaluating longitudinal changes in the SIR especially in regards to their association with surgical interventions, optimal timing of assessment, and their effect on patient survival. Methods: Data from 6 hospitals from January 1998 to December 2012 were retrospectively collected. We examined 2280 patients with complete data. For the subgroup analysis investigating conversion, we examined 587 patients with full preoperative and postoperative data from 21 to 56 days postoperative. Patients were stratified into 4 groups for analysis of conversion in a multivariate Cox-regression model. Results: A longitudinal profile for the perioperative NLR and LMR was clearly characterized identifying an optimal period of remeasurement at 21 to 56 days postoperation. In multivariate analysis both NLR change group ( P < 0.001) and LMR change group ( P < 0.001) were independently associated with overall survival. For both biomarkers, patients with both a low preoperative and postoperative inflammatory state had the best survival. A change from the preoperative to postoperative inflammatory state was associated with a survival difference. Conclusions: This study characterizes the perioperative SIR profile and provides evidence for the remeasurement of SIR biomarkers postoperatively at 21 to 56 days for further prognostication.